The Relationship between Sami and Nordic Peoples Expressed in Terms of Family Associations - Mundal, Else (Journal of Northern Studies, 2010)
The article investigates motifs from medieval sources and sources from early modern times in which the relationship between the Sami people and their Nordic neighbours is expressed in terms of family associations. During Romanticism it became a custom among Scandinavians to speak about each other as broderfolk, which in English is sister nations. In Old Norse sources it was the Sami people who were spoken of as “family,” but of a slightly more distant type than siblings. Haraldr hárfagri, who united Norway, married a Sami girl, Snæfríðr. Their marriage, which was a complicated one, may be seen as a symbolic expression of the problematic and loving relationship between two peoples. The king was the foster-son of the Sami people. To express the relationship between two peoples in terms of foster-child/foster-parent relations creates a picture with a very clear symbolic meaning. The kings of Norway from Haraldr harðráði on traced their family back to a Sami girl, and the earls of Hlaðir traced their family back to Sæmingr, probably the Proto-Sami. It may have been important, at least as a symbolic expression of community, that the princely houses of Norway had family roots in both peoples of the kingdom.